Unforeseen Developments, GATT Obligations and South Africa’s Safeguard Investigations - Brink, Gustav (Comparative and International Law Journal of Southern Africa, 2024)
South Africa is one of the oldest users of trade remedies in the form of anti-dumping and countervailing, but is a newcomer to the use of safeguards. Since increasing its use of safeguards in 2012, the country has become one of the biggest users of safeguards. To date, South Africa has completed nine safeguard investigations, six of which resulted in the imposition of safeguard measures. In conducting safeguard investigations, attention must be given to various aspects. This article considers the requirements that there must have been a surge in imports as a result of unforeseen developments and General Agreement on Tariffs and Trade 1994 (GATT) obligations. While several of the International Trade Administration Commission of South Africa (the Commission) reports set out the current tariff position, few of them indicate what South Africa’s GATT obligations are, thus falling short of the requirements to impose measures. The article shows that few, if any, of South Africa’s safeguard investigations have evaluated unforeseen developments in line with the requirements of GATT, as interpreted by the World Trade Organization (WTO) Dispute Settlement Body, as many of these alleged developments either did not relate to the subject product or were not, in fact, unforeseen. The article further shows that the Commission has failed, in every investigation, to link the unforeseen developments and GATT obligations to the surge in imports, as often the unforeseen developments occurred years prior to any increased imports. Finally, the article proposes that the Commission amend its method of analysing unforeseen developments and increased efforts be made to establish the link between these developments and GATT obligations and the increased imports.